Analisis Pengaruh Customer Service, Online Customer Review, Media Sosial, Dan Brand Image Terhadap Minat Beli Pada Marketplace Shopee (Studi Kasus Mahasiswa Di Kota Malang) - Kofifah Indria Novitasari; Rois Arifin; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2023)
Abstract This study aims to examine customer service, online customer reviews, social media, and brand image on buying interest in the shopee marketplace (a case study of students in the city of Malang). The population in this study are students in the city of Malang who have an interest in buying at the shopee marketplace. The sampling technique used quantitative methods with a sample of 65 respondents. The analytical method used is multiple linear regression analysis with SPSS application tools. This study has met the requirements of the classical assumption test, multiple linear regression, hypothesis testing, and analysis of the coefficient of determination. The variables used in this study are buying interest (the dependent variable), while customer service, online customer reviews, social media and brand image (independent variables). The results of the study show that simultaneously the variables of customer service, online customer reviews, social media, and brand image simultaneously influence purchase intention. Partially, the variables of customer service and social media have an effect on purchase intention as well as online customer review variables, and brand image partially has no effect on purchase intention because the significant value is greater than 0.05 and the t-count <1.402 Keywords: Customer Service, Online Customer Reviews, Social Media, Brand Image